2004
DOI: 10.1002/chem.200400215
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity in Iron‐Catalyzed [2+2+1] Cycloadditions: A DFT Investigation of Substituent Effects in 1,4‐Diazabutadienes

Abstract: The transition-metal-catalyzed [2+2+1] cycloaddition reaction of 1,4-diazabutadienes, in which the imine-carbon atoms are part of an oxazine ring system, with ethylene and carbon monoxide leads to the regioselective formation of pyrrolidinone derivatives. To explain this regioselectivity, the transition states and intermediates of the rate-determining step of the catalysis are determined by high-level DFT calculations. The experimentally observed regioselectivity is consistent with the lower activation energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The reaction of an imine instead of a 1,4-diazabutadiene under the same conditions only proceeded with lower selectivity. This result revealed that the ketimine functionality acted as a bidentate ligand and subtle substituent effects were responsible Scheme 24 for the regioselectivity, as also suggested by the theoretical studies [53].…”
Section: Scheme 23supporting
confidence: 65%
“…The reaction of an imine instead of a 1,4-diazabutadiene under the same conditions only proceeded with lower selectivity. This result revealed that the ketimine functionality acted as a bidentate ligand and subtle substituent effects were responsible Scheme 24 for the regioselectivity, as also suggested by the theoretical studies [53].…”
Section: Scheme 23supporting
confidence: 65%
“…A catalytic version has only been reported by Imhof et al for the hetero-Pauson–Khand cycloaddition of cyclic imidates, carbon monoxide, and ethylene catalyzed by nonacarbonyldiiron (Scheme ). A second imine moiety was required in proximity to the reacting imidate, suggesting that the substrate acts as a bidentate ligand for the iron. Computational results revealed that the ethylene will always attack the less stable imine group with less efficient delocalization of π-electron density.…”
Section: Cycloadditions and Alder-ene-type Reactionsmentioning
confidence: 99%
“…Previous investigations indicated that the B3LYP method can give reasonable structures and energies for iron-containing reactions. All the stationary points on the potential energy surface (PES) were optimized on the quartet and sextet spin states first using the hybrid density functional B3LYP method with the 6-31+G(d) basis set. , Meanwhile, the test of stability of the density functional theory (DFT) wave function was passed. If an instability is found, the wave function is reoptimized, and the stability tests and reoptimizations are repeated until a stable wave function is found.…”
Section: Theoretical and Experimental Detailsmentioning
confidence: 99%